A thermal-assisted electrochemical strategy to synthesize carbon dots with bimodal photoluminescence emission. (30th June 2022) - Ran, Qingqiang; Wang, Xuepeng; Ling, Peng; Yan, Peiwen; Xu, Jun; Jiang, Long; Wang, Yi; Su, Sheng; Hu, Song; Xiang, Jun
Abstract: Although several groups have reported bimodal emissive carbon dots (B-CDs) and paid considerable attention to their ratiometric fluorescent sensing application in recent years, the establishment of convenient yet robust strategies that can generate B-CDs from various low-cost and extensive carbon sources is still required. Here a novel thermal-assisted electrochemical strategy for preparing B-CDs from low-cost carbon sources, including graphite and raw coal, is reported. The as-prepared B-CDs exhibit bimodal photoluminescence (PL) emission at 415 and 510 nm under single-wavelength excitation. Furthermore, the origination of the bimodal emissive characteristics of the as-prepared B-CDs was investigated in detail. Under thermal induction, the carbonyl-related surface state PL centers are generated at the surface of B-CDs, and the co-existence of the carbonyl-related surface state and core state PL centers results in bimodal PL emission. Finally, to demonstrate its practical application, a ratiometric PL nanoprobe was developed to sense pH. This thermal-assisted electrochemical strategy is versatile and potentially suitable to a wide range of low-cost carbon sources. Graphical abstract: A thermal-assisted electrochemical oxidation strategy is developed to produce bimodal photoluminescence emissive carbon dots from the blocky graphite. Under thermal induction, the carbonyl pairs are generated at the surface of carbon dots, and the co-existence of the carbonyl-related surface state and core state PL centers results in bimodal PL emission. This approach is versatile, and potentially suitable to a wide range of low-cost carbon sources. Image 1 Highlights: A novel thermal-assisted electrochemical strategy for synthesizing B-CDs was designed. The effect mechanism of thermal induction on PL properties of the B-CDs was discussed. B-CDs have an ultra-high stability under different environmental conditions. B-CDs can be used as a ratiometric probe to monitor pH.